Avaliação da capacidade e comprometimento funcional em pacientes traqueotomizados de um hospital público de Curitiba - Gomes, Regina Helena Senff (2014)
INTRODUCTION: tracheotomized patients after long period of hospitalization and mechanical ventilation present changes in their functional performance. It is necessary to determine their degree of dependence in order to assess which daily activities feature the highest deficit to guide multidisciplinary team intervention, to point impairments at the moment of hospital discharge, and signal the need of a caregiver. OBJECTIVE: to assess and describe degrees of functional performance and impairment in tracheotomized patients at a public hospital in Curitiba, Paraná State/Brazil, to assess and describe the interrelationship between functional performance and impairment. METHODOLOGY: quantitative, descriptive, crosscut, case-control study. This study was held at a hospital of tertiary reference linked to the Unified Health System. Functional performance and impairment were assessed by means of Barthel Index and Karnofsky Performance Scale in tracheotomized and non-tracheotomized patients admitted to Internal Medicine, Infectology, Neurosurgery and Neurology. The study group was paired to the control group considering age, sex, and disease which caused the hospitalization. RESULTS: the sample consisted of 26 tracheostomized and 26 non-tracheotomized patients, among them, 30 male patients and 22 female patients. Average age in the study group was 55.4 years (SD – 15.6), and 55.1 years of age (SD – 14.1) in the control group. Statistical analysis of Barthel Index in the study group rated 84.62% of the patients as totally dependent to carry on 10 domains of the instrument, unlike control group where only 15.38% of the patients presented this degree of physical dependence, while 53.85% feature total independence to carry on the same activities. The assessment by Karnofsky Scale evidenced that 57.69% of the study group scored 40%, which signals impairment and need of special care and assistance, different from the control group where 42.31% scored 90%, being able to lead a normal life with very few signs or symptoms of disease. CONCLUSIONS: There was a large implication of functional performance and impairment in tracheotomized patients, which demands a new look on the part of the multidisciplinary team at the identified disabilities, showing that despite the facilitation of mechanical ventilation weaning, hospitalization causes a major impact on patients’ quality of life.